2014
DOI: 10.1097/mao.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Changes in the Cochlea Associated With Diabetes Mellitus—A Review

Abstract: There seems to be variable vulnerability of different cochlear cell types to the DM state. Further studies are required to determine the factors responsible for the differences in the histopathologic observations of cochlear tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 77 publications
3
67
0
6
Order By: Relevance
“…There was no consensus in the literature study on the characteristics of hearing loss associated with the DM; it is believed that the variations found could be related to inner ear affected region. Although many studies point to the existence of histopathological cochlear alterations in DM, it is difficult to establish a causal relationship, highlighting the differential vulnerability of inner ear to the effects of hyperglycemy 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no consensus in the literature study on the characteristics of hearing loss associated with the DM; it is believed that the variations found could be related to inner ear affected region. Although many studies point to the existence of histopathological cochlear alterations in DM, it is difficult to establish a causal relationship, highlighting the differential vulnerability of inner ear to the effects of hyperglycemy 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Constant blood glucose levels can affect the heart and blood vessels, eyes, kidneys and nerves 3 . Changes in the inner ear are also identified in some studies, in which they observed changes in the basement membrane of the capillaries of the vascular stria and the basilar membrane, remarkably thickened, giving rise to diabetic microangiopathy 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores encontraram associação positiva entre a presença da diabetes e comprometimento auditivo (Kakarlapudi et al, 2003;Delgado e Puig, 2003;Bainbridge et al, 2008;Mitchell et al, 2009;Uchida et al, 2010;Akinpelu et al, 2014); Horikawa et al, 2013;Sunkum and Pingile, 2013;Botelho et al, 2014;Kiakajouri et al, 2014), enquanto outros não verificaram esta associação (Harner, 1981;Hodgson et al, 1987;de Espanã et al, 1995;Dalton et al, 1998). Alguns autores sugeriram que esta controvérsia pode estar relacionada à presença de muitas variáveis de confusão, bem como à complexidade do sistema auditivo (Uchida et al, 2010;Asma et al, 2011).…”
Section: Limiares Auditivos -Comparação A1 Com A2unclassified
“…Podemos hipotetizar que a maior piora auditiva no grupo HA durante este período de 3-4 anos, pode estar relacionada ao maior tempo da doença neste grupo, se considerarmos que esta patologia causa insuficiência microcirculatória, que pode determinar uma maior ou menor deterioração do sistema auditivo periférico (Carrasco et al, 1990 Alguns autores já descreveram que as frequências mais prejudicadas nos indivíduos diabéticos (Harner, 1981;Ishii et al, 1992;Cullen e Cinnamond, 1993;Ciorba et al, 2011;Akinpelu et al, 2014) e nos hipertensos (Brant et al, 1996;Carmo et al, 2008;Sahin-Yilmaz et al, 2012) são as altas. Além disso, sabe-se que a presbiacusia também compromete, de forma mais evidente, as frequências altas (Gacek e Schuknecht, 1969).…”
Section: Limiares Auditivos -Comparação A1 Com A2unclassified
See 1 more Smart Citation